Analysis of human resources management in family health, community and intercultural models in Andean countries - Bustos, Verónica (2015)
Introduction: While stressing the importance of health workers in sufficient quantity and quality, the member states of the Andean Health Organization - Hipólito Unanue Agreement (ORAS / CONHU) have launched initiatives aimed at generating and disseminating knowledge on policies, strategies and models of human resource management. Objective: To analyze the component of Human Resources for Health Management, identifying models used and their contribution to the set up of a health system based on primary care. Design: Qualitative study. Location: Ministries of Health of the Andean countries. Participants: Managers of Human Resources. Interventions: Design and implementation of a tool for qualitative analysis. Results: Countries have made progress in developing systems for managing human resources for health. They acknowledge that persistent problems include staff shortage and maldistribution, as well as professional graduate profiles not fully meeting population health needs derived from epidemiological change and a growing commitment to universal health coverage. Conclusions: Innovative strategies for planning, training and performance management could help to address the problems of human resources for health in a proper context of leadership and governance.